Antikörper gegen Remicade-Infliximab reagieren auch bei Biosimilars (Aktuelle Rheumatologie, 2017)
Ruiz-Argüello MB et al. Antibodies to infliximab in Remicade-treated rheumatic patients show identical reactivity towards biosimilars.